Profile of Student Problems in Class VIII of 39 Padang State Junior High School - Syafrinda, Desi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
This research is motivated by the presence of students who follow a friend's invitation to skip class when they are not liked, there are students who are late because they are waiting for their friends, there are students who do not collect assignments because their friends have not collected assignments. studied in class VIII Class XI Department of Software Engineering SMK N 1 Lubuk Attitude seen from: 1) Conformity without consideration. 2) Identification conformity. 3) Internalization conformity. This research was conducted using a quantitative descriptive method. The research population was 67 students who were selected by total sampling technique. The instrument used is a questionnaire. Meanwhile, for data analysis using percentage classification. Based on the results of research on the conformity profile of peers in learning in class VIII Class XI of the Department of Software Engineering at SMK N 1 Lubuk Attitude, it can be seen from: 1) Conformity without consideration is in the fairly high category. 2) The conformity of identification is in the fairly high category. 3) Internalization conformity is in a fairly high category. The results of this study are recommended for students to believe in themselves in order to avoid negative conformity to peers.